Situation analysis of the social enterprises engaged in refractive error services delivery in Kenya - Shadrack Muma; Kovin Shunmugam Naidoo; Rekha Hansraj (BMC Health Services Research)
Abstract Aim To conduct a situational analysis of the social enterprises (SEs) engaged in refractive error services delivery in Kenya. Methods This was a sequential mixed method study conducted with commercial enterprises (CE), eye care professional’s representatives from the Ministry of Health ophthalmic service unit and representatives from SEs. The study was undertaken in two phases with phase one aimed at identifying the SEs while phase two aimed at exploring the SEs. The participants were recruited purposively and through snowball sampling with data collected telephonically and through online Google form survey. The qualitative data was collected until thematic saturation was achieved. The descriptive data was presented in figures, as well as reported in terms of frequencies. Results Out of the 196 (28%) CE, only 49 (7.1%) reported referral and vision screening as some of the support they provide to SEs. The key barrier to SE integration into refractive error service delivery in conjunction with other eye care providers in Kenya, was lack of awareness on SE (n = 12; 41.4%) while cash flow was noted as the least cited barrier to SEs integration (n = 2; 13.8%). Reasons for the success of SE in the broader eye health ecosystem constituted mission, leadership skills and creativity. Policy regulation reported by the SE representatives (n = 14; 48.3%) was the key factor influencing the operations of SEs in Kenya. Factors negatively influencing integration of SE into refractive error service delivery in Kenya were categorized into unhealthy competition, inadequate human resources, predator SE (n = 19; 65.5%) and lack of proper policy regulation. Partnership, technology, cross-subsidization and skills development were identified as ideal for SE integration. Conclusion This study found that SEs are worthy for integration into the eye health ecosystem to complement the dominant CE for effective refractive error service delivery. However, establishment of policies recognizing SEs and integration into the eye health ecosystem is desirable to address the challenges experienced by the SEs.